Penerapan Prinsip Free, Prior, And Informed Consent oleh Direksi dalam Investasi Berbasis Sumber Daya Alam - Natal Frantomas Nababan; Martono Anggusti; Samuel F. B. Situmorang (Fakultas Hukum Universitas Riau, 2026)
This article aims to analyze the position and implementation of the principle of Free, Prior, and Informed Consent (FPIC) in forestry business activities that intersect with the rights of indigenous peoples, and examine its relationship with the principles of Good Corporate Governance and the fiduciary obligations of directors in managing legal and social risks. The main issues discussed are the extent to which the national legal system substantively accommodates FPIC and how fragmented norms and weak institutional coordination hinder its implementation in practice. This research uses normative legal research methods with legislative, conceptual, and case study approaches to examine the relationship between international standards, national legal frameworks, and corporate practices in the forestry sector. The main findings indicate that FPIC in the national legal system is still partially constructed and tends to be reduced to a formalistic consultation mechanism, so it does not yet function as a substantive agreement that provides an equal bargaining position for indigenous peoples. This condition is exacerbated by regulatory fragmentation and weak institutional coordination, which leads to a lack of synchronization between the licensing process and the recognition of indigenous territories. This article contributes to strengthening the argument for the need to strengthen legal substance, institutional structures, and legal culture so that corporate governance in the forestry sector is more equitable, sustainable, and respects the rights of indigenous peoples.